Portraits of Little Women - Pfeffer, Susan Beth (New York : Delacorte Press, 1997)
Relates ten-year-old Beth's exciting trip to pre-Civil War New York City with Marmee and Father.
Keywords: Sisters -- Fiction; Family life -- Fiction